Delivery of an LGA infant and the maternal risk of diabetes: A prospective cohort study. Issue 4 (August 2018) - Hakkarainen, Heidi; Huopio, Hanna; Cederberg, Henna; Voutilainen, Raimo; Heinonen, Seppo
Highlights: GDM women with LGA infants are at increased risk for subsequent T2DM. GDM women with LGA infants represent a target group for T2DM prevention. LGA delivery in the absence of GDM does not predict later T2DM. Abstract: Aims: Was to determine whether the birth weight of the infant predicts prediabetes (impaired fasting glucose, impaired glucose tolerance, or both) and type 2 diabetes (T2DM) during long-term follow-up of women with or without gestational diabetes mellitus (GDM). Methods: The women with or without GDM during their pregnancies in Kuopio University Hospital in 1989–2009 (n = 876) were contacted and invited for an evaluation. They were stratified into two groups according to the newborn's birth weight: 10–90th percentile (appropriate-for-gestational-age; AGA) (n = 662) and >90th percentile (large-for-gestational-age; LGA) (n = 116). Glucose tolerance was investigated with an oral glucose tolerance test after a mean follow-up time of 7.3 (SD 5.1) years. Results: The incidence of T2DM was 11.8% and 0% in the women with and without GDM, respectively, after an LGA delivery. The incidence of prediabetes increased with offspring birth weight categories in the women with and without GDM: from 46.3% and 26.2% (AGA) to 52.9% and 29.2% (LGA), respectively. Conclusions: GDM women with LGA infants are at an increased risk for subsequent development of T2DM and therefore represent a target group for intervention to delay or prevent T2DM development. In contrast, an LGA delivery without GDM does not increase T2DM risk.